Review on microbial 1, 3-propanediol production: Emerging strategies, key hurdles and attainable solutions to re-establish its commercial interest - Nimbalkar, Pranhita R.; Dharne, Mahesh S. (Industrial Crops and Products, 2024)
1,3-propanediol (1,3-PDO) is a vital value-added bi-functional compound that has numerous uses in the industrial sector including the polymer, pharmaceutical, food, and cosmetics industries. 1,3-PDO biosynthesis from renewable resources through green methods has received considerable attention. However, technical difficulties such as low product titer, by-product accumulation, and incomplete substrate consumption impede its sustainable production at the industrial scale. Hence, understanding the overall 1,3-PDO process development with integrated knowledge of techno-economics would help to build more production facilities across the world. In this view, the biotechnological production of 1,3-PDO is systematically reviewed briefing the synthesis routes, microbial strains, metabolic pathways, and fermentation modes along with several purification strategies. The present review also summarizes key hurdles in 1,3-PDO production and discusses the attainable solutions to achieve higher product titer. Finally, the economic viability of 1,3-PDO biosynthesis is described based on the existing research.
Keywords: 3-Propanediol; Fermentation processes; Glycerol; Purification strategies; Techno-economical assessment